Rancang Bangun Aplikasi Ppdb Di Mts Riset Fathul Huda dengan Metode Rad Berbasis Web - Fajar, Nugroho Gusti Bintang; Budiman, Saiful Nur; Febrinita, Filda (Jurnal Sains dan Teknologi (JSIT), 2025)
The New Student Admissions (PPDB) process at MTs Riset Fathul Huda has been carried out manually, resulting in various obstacles such as time inefficiency, potential data input errors, and difficulties in managing prospective student files. To overcome these problems, this study aims to design and build a web-based PPDB application using the Rapid Application Development (RAD) method. The RAD method was chosen because it is iterative and fast, and actively involves users in every stage of system development. The resulting application has various main features, including online registration, document upload, payment verification, and data management by the committee. System testing was carried out comprehensively through Black Box Testing, White Box Testing, and User Acceptance Test (UAT). The Black Box test results showed a functional success rate of 96.55%, while the White Box results showed a Cyclomatic Complexity (V(G)) value of 141, all of which have been tested. In addition, the UAT results showed a very high level of user satisfaction, namely 96% from the admin side and 93.33% from the applicant side. Based on the evaluation results, it can be concluded that the developed web-based PPDB application is feasible, efficient, and well-received by users. It can also be an effective solution for digitizing student admissions at MTs Riset Fathul Huda